Phanerozoic environmental changes in the Caucasus and adjacent areas: stratigraphy, fossil diversity, mass extinctions, sea-level fluctuations, and tectonics - Eriksson, Patrick George (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 2009.